(untitled) (Baghdad Science Journal, 2023)
A simple, sensitive and accurate spectrophotometric method has been developed for the determination of salbutamol sulphate (SAB) and isoxsuprine hydrochloride (ISX) in pure and pharmaceutical dosage. The method involved oxidation of (SAB) and (ISX) with a known excess of N-bromosuccinamid in acidic medium, and subsequent occupation of unreacted oxidant in decolorization of Evans blue dye (EB). This, in the presence of SAB or ISX was rectilinear over the ranges 1.0-12.0, 1.0-11.0 µg/mL, with molar absorptivity 4.21×104 and 2.58×104 l.mol-1.cm-1 respectively. The developed method had been successfully applied for the determination of the studied drugs in their pharmaceutical dosage resulting in a good agreement with certified value and standard addition procedure.